A STUDY ON THE ORIENTATION OF SELECTED ETHNIC COMMUNITIES TOWARDS BUSINESS ETHICS )AN EMPIRICAL STUDY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The paper makes an effort to study the role of  four theoretical approaches to business ethics  under consideration namely Utilitarianism,  Managerial egoism, Deontological Ethics and  Virtue Ethics on three prominent ethnic groups  namely Bodo, Mishing and Rabha. The study  was exploratory cum descriptive in nature and  conducted on a sample of 1200 respondents  comprising of 400 respondents from each  community. Stratified cum convenience  sampling technique was used with a structured  questionnaire schedule for field study in the  state of Assam.  The field study found that the people of the  Bodo community are highly influenced by  Managerial Egoism and Deontological Ethics  whereas the people of the Mishing community  are highly influenced by Utilitarianism and  Virtue Ethics. Lastly the people of the Rabha  community are influenced by a mixture of  Managerial Egoism, Deontological Ethics  and Virtue Ethics. These are vital input for  managers in taking important decisions in the  field of management.
Keywords: ethnic; ethics; egoism; utilitarianism; deontology